2023
DOI: 10.1080/14756366.2023.2171030
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin – stratification biomarker in diastolic cardiac dysfunction

Abstract: This study does not propose to elucidate how adiponectin secretion is regulated, but how its adiponectin concentration is an indicator of heart disease. About adiponectin, it is not known whether it is functionally an enzyme, or very likely a cytokine/chemokine/hormone, secreted by fat cells/adipocytes in the abdomen. Abdominal fat secretes 67 hormones, and all of which cause disease. For example, adiponectin generates diabetes and ischaemic heart disease via dyslipidemia. Based on clinical symptoms, electroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…In the development of metabolic disorders, the proliferation of preadipocytes due to chronic adipocyte inflammation, fatty acid oxidation, or accumulation of cellular damage can trigger ROS. Furthermore, adiponectin promotes high LDL and low HDL concentrations and shows a negative association with BMI, but a positive association with pro-inflammatory cytokines, such as TNF-α and IL-6 [19][20][21]. The lipid profile results obtained in our study were similar to those reported by other Authors who also studied young individuals with T1DM [10,22,23].…”
Section: Discussionsupporting
confidence: 89%
“…In the development of metabolic disorders, the proliferation of preadipocytes due to chronic adipocyte inflammation, fatty acid oxidation, or accumulation of cellular damage can trigger ROS. Furthermore, adiponectin promotes high LDL and low HDL concentrations and shows a negative association with BMI, but a positive association with pro-inflammatory cytokines, such as TNF-α and IL-6 [19][20][21]. The lipid profile results obtained in our study were similar to those reported by other Authors who also studied young individuals with T1DM [10,22,23].…”
Section: Discussionsupporting
confidence: 89%